2009
DOI: 10.1001/archoto.2008.531
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriology of Chronic Rhinosinusitis With and Without Nasal Polyps

Abstract: There are no significant differences in the bacteriologic features of ethmoidal biopsy specimens between CRSNP+, CRSNP-, and control patients. Therefore, a bacteriologic pathogenesis of the polyps in CRSNP+ patients seems unlikely. The general use of antibiotics in patients with CRS appears questionable. Investigation of nasal lavage samples is not suitable for predicting the bacteriologic features of inflamed sinuses of patients with CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 19 publications
9
47
2
5
Order By: Relevance
“…The pattern of bacterial isolates in our patients with CRS, either with or without polyposis, is similar to previous publications [7,10,11,12,13,14,15,16,17,21,22,23,24]. There was a high rate of aerobic pathogens, especially S. aureus and enteric bacteria, such as P. aeruginosa , and anaerobic species of Streptococcus and Proprionibacterium.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The pattern of bacterial isolates in our patients with CRS, either with or without polyposis, is similar to previous publications [7,10,11,12,13,14,15,16,17,21,22,23,24]. There was a high rate of aerobic pathogens, especially S. aureus and enteric bacteria, such as P. aeruginosa , and anaerobic species of Streptococcus and Proprionibacterium.…”
Section: Discussionsupporting
confidence: 89%
“…However, the bacteria isolated from patients with CRS with and without nasal polyposis [11,12,13,14,15] have been compared in only a few studies, conducted mainly in the United States, Europe, and the Far East. The characterization of sinus bacteriology in the Middle East has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the bacterial pathogens associated with chronic sinusitis, but the great majority of them included only a small, or indeterminate, number of patients with odontogenic infection (Kremer et al, 2001;Finegold et al, 2002;Aral et al, 2003;Niederfuhr et al, 2009), or did not test the antimicrobial susceptibility of these bacteria (Brook, 2005). While it is reported that the sinusitis of dental origin is polymicrobial and caused by bacteria from the oral cavity and from the upper airways (Mehra & Jeong, 2009), some aspects, such as the role of anaerobic bacteria in this infection, are not well studied and would need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Результаты исследований свидетельствуют о том, что бактериальная флора околоносовых пазух здо-ровых добровольцев и пациентов с ХР во многом схожа [23]. Тем не менее у пациентов с ХР при микробиологиче-ском исследовании микрофлоры околоносовых пазух отмечаются повышенная концентрация микроорганиз-мов, склонных к образованию биопленок, более частое высевание Staphylococcus aureus, включая метициллинре-зистентные штаммы, особенно у пациентов с сопутствую-щим диабетом, а также наличие анаэробных полирези-стентных микроорганизмов в сочетании с грамотрица-тельной флорой [24].…”
Section: хронический риносинусит (хр)unclassified